Information System Development Using Microsoft Visual Studio to Speed Up Approved Sample Distribution Process - Carolline Audrel Vellicia Wijaya; Hery Hamdi Azwir (JIE Scientific Journal on Research and Application of Industrial System, 2020)
An approved sample is a sample that has been tested in a laboratory and approved by experts who understand it to be a sample in the production process. In the current process, all sample identities are written manually and repeatedly inputted by several people. This manual process is a major bottleneck in producing approved samples so that it can cause delays in the production process. This manual process causes employees to have to work overtime 2-3 hours every day to complete the approved sample which must be issued on the same day. To overcome this problem, an information system was developed to eliminate bottlenecks in this process. Design and development of software use the SDLC method which includes information gathering to find out business processes, DFD analysis, design user interface, ERD and database, and continued with development using Visual Studio, Microsoft Access, Microsoft Excel, and VBA as well as Microsoft Outlook as supporting programs. After the software is implemented it can be seen that the bottlenecks that have occurred so far can be removed and the work completed faster, no additional overtime is required and can even be one day sooner. Besides all the data is stored more neatly and facilitates the process of finding data.